Measuring shear wave velocity using bender elements - Leong, Eng Choon (2011)
The use of bender element to measure shear wave velocity is popular due to its simplicity. However, there are still some uncertainties in the interpretation of the bender element test. In this paper, the use of bender elements in the determination of shear wave velocities of dry, unsaturated, and saturated soil specimens is examined with respect to the characteristics of the bender elements, waveform, magnitude, and frequency of the applied voltage to the transmitter bender element and method of travel time determination. The interpretation of the bender element test can be improved if two performance criteria are adopted: (1) a signal-to-noise ratio of at least 4 dB for the receiver signal, and (2) a wave path length to wavelength ratio of at least 3.33. Procedures to estimate the strain level associated with the shear wave velocity measurement using bender element are also described.